DEVELOPMENT OF PROFESSIONAL COMMUNICATIVE COMPETENCE OF ECONOMICS STUDENTS IN ENGLISH LANGUAGE TEACHING - Komilova, Dildora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article discusses the development of the professional competence of future economists in the teaching of English in the higher education system with the help of modern methods and technologies. Also, the essence of the concept of professional competence and ways of its development, the importance and role of educational technologies, the role of a foreign language in preparing for professional activity and its role in the formation of sectoral communicative competence are highlighted.